y=3(4)*-1

Simple and best practice solution for y=3(4)*-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=3(4)*-1 equation:


Simplifying
y = 3(4) * -1

Multiply 3 * 4
y = 12 * -1

Multiply 12 * -1
y = -12

Solving
y = -12

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -12

See similar equations:

| x=180-(7x-12) | | -7(-1+3x)=5(3-5x) | | 35(8x-20)-18=-718 | | 6(x-4)=-5(2x+2) | | m^2-8m-33=0 | | x+3+2x+5=19 | | l^2-6l-91=0 | | -6-x=15+2x | | 3p(-4)=13 | | 3(x-2)+4=2x+6 | | 13.95x=558 | | 5x/2+x/2+2=3x | | x+(x+2)=0 | | 15-3(6-2c)= | | 13b+44=4 | | 2(x+3)=3-x | | 3-5(2x+3)=20 | | -5y+7=-2(y-5) | | -z=40 | | 6x+5-3x=-22 | | 13.95x=279 | | 6y^2-15y=0 | | 20=-x | | 5n=6 | | 3b+25=8(10+b) | | a/2=2 | | -8=6n-3-7n | | 6*2-0.5*24= | | x/4-3=2x/5 | | 2x=2.6+1.4 | | 1-32x=2+31x | | -3(36+7x)=-66 |

Equations solver categories